Creating an Undergraduate Literary Journal : A Production Guide for Students and Faculty - Colombe, Audrey (Audrey A.) (Bloomsbury Academic, 2022)
"University literary journals allow students to create their own venue for learning, have a hands-on part of their development in real-world skills and strive towards professional achievement. But producing an undergraduate literary magazine requires commitment, funding and knowledge of the industry. This practical guide assists students and faculty in choosing a workable structure for setting up, and then successfully running, their own literary publication. Whether the journal is print or online, in-house or international, Creating an Undergraduate Literary Journal is a step-by-step handbook, walking the reader through the process of literary journal production. Chapters focus on: defining the journal; the financial logistics; editing the journal; distribution; and what could come next for a student writer-editor after graduation. The first book of its kind to offer instruction directly to those running university-based literary magazines, this book includes insights from former editors, advisers, students and features an extensive list of active student-run literary magazines key literary organizations for writers/ editors who serve literary publications. From Audrey Colombe, faculty adviser on the award-winning Glass Mountain magazine from the University of Houston, this is a text for both newcomers and those more informed on the production process to help them navigate through a successful publishing experience"--